2020
DOI: 10.1017/s0007114520004079
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the inflammatory potential of the Brazilian population’s diet

Abstract: Objectives: To assess the inflammatory potential of the Brazilian population’s diet and its association with demographic, socioeconomic, and anthropometric characteristics. Methods: Cross-sectional study performed with 34,003 individuals aged 10 and older, evaluated by the National Diet and Nutrition Survey (INA) from the Consumer Expenditure Survey (POF 2008-2009). The Energy-adjusted Dietary Inflammatory Index (E-DIITM) was determined using 34 dietary parameters calculated through non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
2
5
2
2
Order By: Relevance
“…39 Kurklu et al 13 found that the DII mean in Turkish adolescents was 3.6; thus, higher than the mean found among the adolescents of this study. The mean DII of Brazilian adolescents assessed by Pereira et al 17 in a populationbased study carried out in 2008-2009 was 1.42 (95% CI: 1.39-1.46), a value that is higher than the means estimated in this study. Nevertheless, such difference may be attributed to distinct parameters adopted to calculate DII in the two studies.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…39 Kurklu et al 13 found that the DII mean in Turkish adolescents was 3.6; thus, higher than the mean found among the adolescents of this study. The mean DII of Brazilian adolescents assessed by Pereira et al 17 in a populationbased study carried out in 2008-2009 was 1.42 (95% CI: 1.39-1.46), a value that is higher than the means estimated in this study. Nevertheless, such difference may be attributed to distinct parameters adopted to calculate DII in the two studies.…”
Section: Discussioncontrasting
confidence: 84%
“…[11][12][13] Differences in eating habits across countries 14 demand ascertaining the association between the diet inflammatory potential and excess weight among Brazilian adolescents, as well as the factors that possibly interfere in this association, which are subjects scarcely explored in the literature. [15][16][17] Therefore, the present study aims to assess the association between the diet inflammatory potential and anthropometric indicators of adiposity, considering demographic, behavioural, and social characteristics, to provide subsidies to targeting and tailoring actions aiming at promoting healthy eating and reducing the obesity onset at early ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foi observado que altos escores de IID, associou-se aos quartis de renda mais elevados, indivíduos com escolaridade ≥ 9 anos na faixa etária de adultos e adolescentes (PEREIRA et al,2021). A população brasileira consome uma dieta com alto potencial inflamatório, principalmente adolescentes, brancos e aqueles com maior renda e escolaridade.…”
Section: Relação Da Dieta Com Características Sociodemográficas E Háb...unclassified
“…A população brasileira consome uma dieta com alto potencial inflamatório, principalmente adolescentes, brancos e aqueles com maior renda e escolaridade. Dessa forma, sugere-se que o perfil de risco socioeconômico de uma dieta com maior potencial inflamatório em países de média renda é diferente do observado em países de alta renda (PEREIRA et al,2021).…”
Section: Relação Da Dieta Com Características Sociodemográficas E Háb...unclassified